2021
DOI: 10.3389/fcell.2021.711965
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Roles of Eukaryotic Initiation Factor 4A Family Proteins in Human Cancers

Abstract: The dysregulation of mRNA translation is common in malignancies and may lead to tumorigenesis and progression. Eukaryotic initiation factor 4A (eIF4A) proteins are essential for translation, exhibit bidirectional RNA helicase function, and act as RNA-dependent ATPases. In this review, we explored the predicted structures of the three eIF4A isoforms (eIF4A1, eIF4A2, and eIF4A3), and discussed possible explanations for which function during different translation stages (initiation, mRNA localization, export, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 107 publications
2
14
0
Order By: Relevance
“…There are two isoforms of eIF4A in mammals that exhibit a sequence identity of 90-95% and have equivalent biochemical functions: eIF4A1 and eIF4A2 [10, 11]. Both isoforms differ significantly in expression levels in vivo , with eIF4A1 being present in almost all tissues during active cell growth and eIF4A2 mainly in organs with low proliferation rates [12].…”
Section: Resultsmentioning
confidence: 99%
“…There are two isoforms of eIF4A in mammals that exhibit a sequence identity of 90-95% and have equivalent biochemical functions: eIF4A1 and eIF4A2 [10, 11]. Both isoforms differ significantly in expression levels in vivo , with eIF4A1 being present in almost all tissues during active cell growth and eIF4A2 mainly in organs with low proliferation rates [12].…”
Section: Resultsmentioning
confidence: 99%
“…Translation initiation is the rate-limiting step of mRNA translation. It has been proposed that cancer cells become ‘addicted’ due to the increased capacity of cancer cells to cope with metabolic stress and maintain cancer growth [ 18 , 32 ]. EIF4A1 has been reported to directly determine the selective translation of oncoproteins, such as myc, myb, notch, cdk6, bcl-2 and ROCK1, which are critical regulators contributing to cancer survival, proliferation, migration, invasion, metastasis and chemoresistance [ 14 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression patterns of the EIF4A family’s genes have been found in different tumors [ 15 , 16 , 17 ]. Moreover, EIF4A family genes have been closely correlated with immune cell infiltration in different cancers [ 18 ]. They may be related to the dysfunction of the RNA helicase, which results in the expression of proteins produced by abnormal RNA translation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other eIF4 factors that have received more investigative attention, the role played by eIF4B in breast cancer is largely unclear. Being a well-appreciated co-activator of eIF4A helicase activity, eIF4B is often thought to facilitate the oncogenic processes dependent on eIF4A/F-dependent translation, which includes cancer cell proliferation, EMT, resistance to apoptosis, glucose metabolism (71, 72), and, more recently, immune evasion (66). In line with a pro-tumor role for eIF4B, a number of largely in vitro studies have reported detrimental effects of eIF4B silencing on malignant cell survival, proliferation (9), and the ability to resist genotoxic stress (73).…”
Section: Discussionmentioning
confidence: 99%